Effect of NPK and silicon fertilizer on growth, flowering, and nectar of Turnera ulmifolia L. - Mogeret, Sidi; Omar, D.; Hafsah, Nahrawi; Hashimah, Elias; H, Wasli (IOP Publishing, 2022)
Turnera ulmifolia L. is a beneficial plant mostly planted in the oil palm plantation as it is easily adapting to a variety of environmental conditions, mainly to conserve beneficial insects. Nevertheless, the planted plants were left without proper maintenance and less study was conducted on biological control agent conservation. Thus, this study aimed to examine the effect of NPK, silicon fertilizer and their combination on the growth and development of T. ulmifolia. Treatments including T0 Control (No fertilization application), T1 (0.2 g NPK), T2 (0.2 g NPK+3.9 g silicon), T3 (0.2 g NPK+4.9 g silicon), T4 (3.9 g silicon) and T5 (4.9 g silicon) were applied 20 days after transplanting at monthly interval for three months. Results revealed the greatest height and number of branches were observed in T1. Overall, the chlorophyll content ranged between 27.92 to 31.18 SPAD values. All treatments gave the same effect on morphometric measurements on the first 30 days of observation. After 60 days, the greatest value for broad tube width and length was observed in T4 which differs significantly from other treatments. The application of fertilizer in T1, T2 and T3 showed 10-20% promotive effects over the control in the amount of nectar produced per flower. For all three observation periods, a similar trend was recorded for the total sugar concentration in flowers, where the mean total sugar content was between 1.37 and 1.61 mg per flower.